The influence of the size and symmetry of cations and anions on the physicochemical behavior of organic ionic plastic crystal electrolytes mixed with sodium salts. Issue 7 (30th January 2018) - Makhlooghiazad, F.; Guazzagaloppa, J.; O'Dell, L. A.; Yunis, R.; Basile, A.; Howlett, P. C.; Forsyth, M.
Abstract : The influence of cations and anions chemistry on the physicochemical behaviour of OIPCs mixed with Na salts is illustrated. Abstract : The phase behaviour, ionic conductivity, electrochemical stability and diffusion coefficients of mobile components in three organic ionic plastic crystals (OIPCs): triisobutylmethylphosphonium bis(fluorosulphonyl)amide (P1i444 FSI), triisobutylmethylphosphonium bis(trifluromethanesulphonyl)amide (P1i444 NTf2 ) and trimethylisobutylphosphonium bis(trifluoromethanesulphonyl)amide (P111i4 NTf2 ) are compared to study the effect of the anions and cations on phase behaviour and dynamics. The FSI-based OIPC shows lower melting point and higher conductivity values most likely because of the higher degree of charge distributions and weaker ion–ion interactions compared to NTf2 anion-based OIPCs. Cyclic voltammetry of electrolytes consisting of these OIPCs with 70 mol% sodium salt incorporated indicates stable sodium plating/stripping behaviour at 70 and 50 °C for all samples. The magnitude of the peak currents, however, are much higher for the FSI-based electrolyte.